The Long-Term Relationship Between the Rate of Exchange and Inflation in Iraq: An Application of the Vector Error Correction Model - Anwer Mezher Hamdaullah Al-Adhimi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to investigate whether the exchange rates and inflation in Iraq have a long-term equilibrium relationship or not. A dataset of exchange rates and inflation from 2000 to 2020 was used. Johansen’s cointegration test was employed to confirm that there is a long-term correlation between these variables. The Vector Error Correction Model (VECM) was utilized, along with Granger causality tests, to understand the long and short run connections and to determine if the causality flow is bidirectional or unidirectional. The results provided proof of a long-run equilibrium connection among inflation and rates of exchange, with strong evidence of a unidirectional causal flow from rates of exchange to inflation in Iraq.